HIV/AIDS: trends in the Middle East and North Africa region. (March 2016) - Gökengin, Deniz; Doroudi, Fardad; Tohme, Johnny; Collins, Ben; Madani, Navid
Highlights: New HIV infections have been on the rise in the Middle East and North Africa (MENA) region in recent years. There is substantial heterogeneity in HIV epidemic dynamics across MENA, and different risk contexts are present throughout the region. Overall, the major route of infection in the MENA region seems to be sexual transmission, but a range of challenges limit interventions to determine the actual sexual trends. Despite unfavorable conditions, many countries in the region have put significant efforts into scaling up their response to this growing epidemic. Summary: Objectives: To give an overview of the HIV epidemic in the Middle East and North Africa (MENA) region. Methods: Articles on the MENA region were reviewed. Results: The MENA region comprises a geographically defined group of countries including both high-income, well-developed nations and low- and middle-income countries. While the annual number of new HIV infections in Sub-Saharan Africa has declined by 33% since 2005, new HIV infections in the MENA region have increased by 31% since 2001, which is the highest increase among all regions in the world. Moreover, the number of AIDS-related deaths in 2013 was estimated to be 15 000, representing a 66% increase since 2005. However, the current prevalence of 0.1% is still among the lowest rates globally. There is substantial heterogeneity in HIV epidemic dynamics across MENA, and different risk contexts are present throughout the region. Despite unfavorable conditions, many countries in the region have put significant effort into scaling up their response to this growing epidemic, while in others the response to HIV is proving slower due to denial, stigma, and reluctance to address sensitive issues. Conclusions: The HIV epidemic in the MENA region is still at a controllable level, and this opportunity should not be missed.